L’économiste et l’autodétermination du citoyen - Dehem, Roger (L'Actualité économique)

(untitled) (HEC Montréal, 1979)
When involved in politics, the economist ought to make his value judgments explicit. Besides efficiency, personal freedom is often at issue in policy prescriptions. Except for some strong advocates of individual freedom, like Bastiat, Hayek and Friedman, economists have too often had an indifferent attitude towards it. This benign neglect may be dangerous when a minority of ideologically committed citizens is attempting to impose its will on the majority by persuasion. This is consonant with J.J. Rousseau's conception of liberty, which is at odds with the one unconsciously held by the majority of citizens who assume personal self-determination.